2019
DOI: 10.1177/0885066619890324
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Prognosis Factors in Patients With Vena Cava Filters in a Quaternary Medical Center: A 5-Year Retrospective Analysis

Abstract: Background: Indications for inferior vena cava filter (IVCF) placement are controversial. This study assesses the proportion of different indications for IVCF placement and the associated 30-day event rates and predictors for all-cause mortality, deep vein thrombosis (DVT), pulmonary embolism, and bleeding after IVCF placement. Method: In this 5-year retrospective cohort observational study in a quaternary care center, consecutive patients with IVCF placement were identified through cross-matching of 3 databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…While the indications and complications of IVCF implantation have always been a concern, more reasonable indications include symptomatic pulmonary embolism, large floating thrombosis in the iliofemoral vein, and contraindications of anticoagulation therapy. 25 IVCF implantation can not only prevent a fatal pulmonary embolism, but also provides a safety guarantee for interventional catheter thrombolytic therapy. 26 We believe that after thrombolysis, the stenosis of the deep vein lumen is more than 50%, and balloon dilation combined with stent implantation should be done with caution.…”
Section: Discussionmentioning
confidence: 99%
“…While the indications and complications of IVCF implantation have always been a concern, more reasonable indications include symptomatic pulmonary embolism, large floating thrombosis in the iliofemoral vein, and contraindications of anticoagulation therapy. 25 IVCF implantation can not only prevent a fatal pulmonary embolism, but also provides a safety guarantee for interventional catheter thrombolytic therapy. 26 We believe that after thrombolysis, the stenosis of the deep vein lumen is more than 50%, and balloon dilation combined with stent implantation should be done with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Both DVT and PE are collectively referred to as venous thromboembolism (VTE) (Yamashita et al, 2022). Currently, systemic anticoagulation is still the preferred method of prevention for VTE OPEN ACCESS EDITED BY Yang Liu, Hong Kong Polytechnic University, Hong Kong SAR, China patients with underlying PE (Duffett and Carrier, 2017;Arslanbekov et al, 2021;Elias et al, 2021). Recent studies have shown that there is no additional benefit of IVCFs deployment in VTE patients with better anticoagulation therapy (Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%